Four Molecular Superconductors Isolated as Nanoparticles. Issue 24 (16th May 2014) - de Caro, Dominique; Faulmann, Christophe; Valade, Lydie; Jacob, Kane; Chtioui, Imane; Foulal, Soukaina; de Caro, Pascale; Bergez‐Lacoste, Manon; Fraxedas, Jordi; Ballesteros, Belén; Brooks, James S.; Steven, Eden; et al.
Abstract: (TMTSF)2 PF6 and (TMTSF)2 ClO4 Bechgaard salts, (BEDT‐TTF)2 I3, and TTF[Ni(dmit)2 ]2 [TMTSF = tetramethyltetraselenafulvalene; BEDT‐TTF = bis(ethylenedithio)tetrathiafulvalene; TTF = tetrathiafulvalene; dmit = 1, 3‐dithiole‐2‐thione‐4, 5‐dithiolate] are among the most popular molecular superconductors. They are grown as nanoparticles that exhibit properties in agreement with those of the bulk. The shape, size, and homogeneity of particles depend on the stabilizing agent and synthesis conditions. We report on the more recent conditions investigated (i) to produce nanoparticles of 35 nm for β‐(BEDT‐TTF)2 I3, (ii) to reduce the particle size to 10–15 nm for TTF[Ni(dmit)2 ]2 and 3–5 nm for (TMTSF)2 ClO4, and (iii) to improve the growth duration from days to one hour for (TMTSF)2 PF6 . Finally, we report evidence of superconductivity in (TMTSF)2 ClO4 particles. Abstract : Four molecular superconductors have been prepared as nanoparticles by using mainly electrochemical synthesis. Among them, (TMTSF)2 ClO4 (TMTSF = tetramethyltetraselenafulvalene) has been the most studied up to now and, like the bulk single crystals, it exhibits superconductivity.